4
$\begingroup$

How can I calculate limit $$\lim_{x\to \pi/4}\cot(x)^{\cot(4*x)}$$ without using L'Hôpital's rule?

What I have tried so far:

I tried to use the fact that $\lim_{\alpha\to 0}(1 + \alpha)^{1/\alpha} = e$ and do the following: $$\lim_{x\to \pi/4}\cot(x)^{\cot(4 \cdot x)} = \lim_{x\to \pi/4}(1 + (\cot(x) - 1))^{\cot(4 \cdot x)} = \lim_{x\to \pi/4}(1 + (\cot(x) - 1))^{\frac{1} {\cot(x) - 1} \cdot (\cot(x) - 1) \cdot \cot(4 \cdot x)} = \lim_{x\to \pi/4}e^{(\cot(x) - 1) \cdot \cot(4 \cdot x)} = e^{\lim_{x\to \pi/4}{(\cot(x) - 1) \cdot \cot(4 \cdot x)}} $$ But I have problems calculating limit $$\lim_{x\to \pi/4}{(\cot(x) - 1) \cdot \cot(4 \cdot x)}$$ I tried to turn $\cot(x)$ into $\frac{\cos(x)}{\sin(x)}$ as well as turning it into $\tan(x)$, but I do not see any workaround afterwards.

I would appreciate any pieces of advice. Thank you!

$\endgroup$
  • 1
    $\begingroup$ How about a change of variable? It may clarify. $\endgroup$ – dfnu Oct 15 '19 at 11:27
  • 1
    $\begingroup$ I tried to replace t = x - pi/4, thus having x = t + pi/4 and t -> 0, but unfortunately it did not clarify. Anyway, I will try to do the same thing again in case I have messed up. Thank you for your reply $\endgroup$ – alexey_zotov Oct 15 '19 at 11:33
  • 1
    $\begingroup$ @alexey_zotov I think it's the right approach. Then use periodicity of cotangent and sum of angles. $\endgroup$ – dfnu Oct 15 '19 at 11:35
  • 2
    $\begingroup$ Try $u = \cot(x)$; use the double-angle formula for cotangent twice to express $\cot(4x)$ using $u$. (Or use the double-angle formula for tangent, but you still want it using $u$.) Strip out the stuff that's not causing problems, and you're left with $\lim_{u\to1}u^{1/(1-u)}$. I don't know whether you're allowed to use the known value of that limit, however. $\endgroup$ – Toby Bartels Oct 15 '19 at 11:41
  • 1
    $\begingroup$ By graphing, the correct answer is actually $\frac{1}{\sqrt e}$. $\endgroup$ – Toby Mak Oct 15 '19 at 12:05
4
$\begingroup$

$$\lim_{x\to\pi/4}\cot x^{\cot4x}=\left(\lim_{x\to\pi/4}(1+\cot x-1)^{1/(\cot x-1)}\right)^{\lim_{x\to\pi/4}{\cot4x(\cot x-1)}}$$

The inner limit converges to $e$

For the exponent, $$\lim_{x\to\pi/4}\cot4x(\cot x-1)=\lim_{x\to\pi/4}\dfrac{\cos4x}{\sin x}\cdot\lim_{x\to\pi/4}\dfrac{\cos x-\sin x}{\sin4x}$$

Now

$$\lim_{x\to\pi/4}\dfrac{\cos4x}{\sin x}=\dfrac{\cos\pi}{\sin\dfrac\pi4}=?$$

Finally

Method$\#:1$

$$F=\lim_{x\to\pi/4}\dfrac{\cos x-\sin x}{\sin4x}=\lim_{x\to\pi/4}\cos x\cdot\lim_{x\to\pi/4}\dfrac{\cot x- 1}{\sin4x}=\dfrac1{\sqrt2}\cdot\lim_{x\to\pi/4}\dfrac{\cot x- \cot\dfrac\pi4}{\sin4x-\sin\pi}$$

Method$\#:1A$

$$F=\dfrac1{\sqrt2}\cdot\dfrac{\dfrac{d(\cot x)}{dx}}{\dfrac{d(\sin4x)}{dx}}_{\text{at } x=\pi/4}$$

Method$\#:1B$

$$F=\dfrac1{\sqrt2}\cdot\lim_{x\to\pi/4}\dfrac1{\sin x\sin\dfrac\pi4} \cdot\lim_{x\to\pi/4}\dfrac{\sin\left(\dfrac\pi4-x\right)}{\sin4\left(\dfrac\pi4-x\right)}=\dfrac{\sqrt2}4$$

Method$\#:2$

set $\dfrac\pi4-x=y$ $$F=\sqrt2\lim_{x\to\pi/4}\dfrac{\sin\left(\dfrac\pi4-x\right)}{\sin4x}=\sqrt2\lim_{y\to0}\dfrac{\sin y}{\sin4\left(\dfrac\pi4-y\right)}=\dfrac{\sqrt2}4$$

$\endgroup$
  • $\begingroup$ @dfnu, Please pinpoint the mistake $\endgroup$ – lab bhattacharjee Oct 15 '19 at 11:56
  • $\begingroup$ You may not have $\lim f^g = (\lim f )^{\lim g}$, in particular when $\lim f = \lim g =0$, which is the case of the limits of your answer. $\endgroup$ – mathcounterexamples.net Oct 15 '19 at 11:57
  • $\begingroup$ @labbhattacharjee sorry I just lost track of partial solutions. $\endgroup$ – dfnu Oct 15 '19 at 11:59
  • $\begingroup$ Thank you very much! Your solution helped me a lot $\endgroup$ – alexey_zotov Oct 15 '19 at 12:13
  • $\begingroup$ @mathcounterexamples.net, Here $\lim f=e\ne0$ $\endgroup$ – lab bhattacharjee Oct 15 '19 at 12:28
2
$\begingroup$

I would use the ansatz $$\lim_{x\to \frac{\pi}{4}}\exp(\cot(4x)\log(\cot(x)))$$ $$=\exp\left(\lim_{x\to \frac{\pi}{4}}\frac{\cos(4x)\log(\cot(x))}{\sin(4x))}\right)$$ $$=\exp\left(\lim_{x\to \frac{\pi}{4}}\cos(4x)\lim_{x\to \frac{\pi}{4}}\frac{\log(\cot(x))}{\sin(4x)}\right)$$ $$=\exp\left(-1\lim_{x\to \frac{\pi}{4}}\frac{\log(\cot(4x))}{\sin(4x)}\right)$$

$\endgroup$
2
$\begingroup$

We have that

$$\cot(x)^{\cot(4*x)}=\left[\left(1+(\cot(x)-1)\right)^{\frac1{\cot(x)-1}}\right]^{\cot (4x)(\cot(x)-1)} \to$$

indeed

$$\left(1+(\cot(x)-1)\right)^{\frac1{\cot(x)-1}}\to e^{-\frac12}$$

and by trigonometric identities

$$\cot (4x)(\cot(x)-1)=\frac{\cos^2 (2x)-\sin^2(2x)}{2\cos(2x)\sin (2x)}\left(\frac{1+\cos (2x)}{\sin (2x)}-1\right) \\=\frac{1-2\sin^2(2x)}{2\sin^2(2x)}\left(\frac{1+\cos (2x)-\sin(2x)}{\cos (2x)}\right)\to -\frac12$$

since by $y=\frac{\pi}2-2x \to 0$

$$\frac{1+\cos (2x)-\sin(2x)}{\cos (2x)}=\frac{1+\sin y-\cos y}{\sin y}=1+\frac{1-\cos y}{y^2}\frac{y}{\sin y}y\to 1+0=1$$

$\endgroup$
2
$\begingroup$

We substitute $c = \cot(x)$ and we get $$ \lim\limits_{x\to\pi/4} \cot(x)^{\cot(4x)} =\lim\limits_{c\to 1}\; c^{\frac{c^4-6c^2+1}{4c^3-4c}} $$ because $$ \cot(4x) = \frac{\cot^4x-6\cot^2x+1}{4\cot^3x-4\cot x} $$ Then we have $$ \lim\limits_{c\to 1} \;c^{\frac{c^4-6c^2+1}{4c^3-4c}} =\lim\limits_{c\to 1} \;\exp\left(\ln(c) \cdot \frac{c^4-6c^2+1}{4c^3-4c}\right) =\lim\limits_{c\to 1} \;\exp\left(\frac{\ln(c)}{c-1} \cdot \frac{c^4-6c^2+1}{4c^2+4c}\right) \\ =\exp\left(\lim\limits_{c\to 1} \;\frac{\ln(c)}{c-1} \cdot \lim\limits_{c\to 1} \;\frac{c^4-6c^2+1}{4c^2+4c}\right) =\exp\left(1\cdot\frac{-4}{8} \right)= \frac{1}{\sqrt{e}} $$ because $\lim\limits_{c\to 1} \;\frac{\ln(c)}{c-1}$ is the derivative of $\ln(x)$ evaluated at $x=1$, which is $1$.

$\endgroup$
  • $\begingroup$ It's an interesting and profound solution, thank you! $\endgroup$ – alexey_zotov Oct 15 '19 at 12:15
  • $\begingroup$ @alexey_zotov Did you notice that my result is different from the one you accepted? $\endgroup$ – Reinhard Meier Oct 15 '19 at 12:17
  • $\begingroup$ The accepted answer did not provide the result, only the in-between numbers. By multiplying them, I got the same result. I accepted it because it developed the ideas I had already been trying to realize $\endgroup$ – alexey_zotov Oct 15 '19 at 12:21
  • $\begingroup$ @alexey_zotov Oops, I missed that. It is not obvious at the first glance how the results are related. $\endgroup$ – Reinhard Meier Oct 15 '19 at 12:28
1
$\begingroup$

With a subtitution $u = x-\frac{\pi}4$ you get

\begin{eqnarray}\lim_{u\to 0} \left[\frac{\cos\left(u+\frac{\pi}4\right)}{\sin\left(u+\frac{\pi}4\right)} -1\right]\cot(4u+\pi).\end{eqnarray}

Using periodicity and sum of angles you now have

$$\lim_{u\to 0} \left[\frac{\frac{\sqrt{2}}2\cos u - \frac{\sqrt 2}{2}\sin u}{\frac{\sqrt{2}}2\cos u + \frac{\sqrt 2}{2}\sin u} -1\right]\cot(4u).$$

Least common denominator brings you to

$$\lim_{u\to 0} \frac{-\sqrt 2 \sin u}{\frac{\sqrt{2}}2\cos u + \frac{\sqrt 2}{2}\sin u}\cdot \frac{\cos 4u}{\sin 4u}=\frac{-\sqrt 2}{\frac{\sqrt 2}2}\cdot \frac14=-\frac12.$$

Thus your limit is $\frac1{\sqrt e}.$

$\endgroup$
  • 1
    $\begingroup$ Understand! I'll delete the comment. $\endgroup$ – mathcounterexamples.net Oct 15 '19 at 12:10
1
$\begingroup$

You have $\cot(x+y) = \frac{\cot x \cot y -1}{\cot x + \cot y}$

Taking $h = x-\pi/4$ you get

$$\cot x = \cot(\pi/4 + h) = \frac{\cot h -1}{\cot h + 1} = \frac{\cos h - \sin h}{\cos h + \sin h} = 1- 2h +o(h)$$ around zero.

And with $4x = \pi + 4h$

$$\cot(4x) = \cot(\pi + 4h) = \frac{\cos(\pi+4h)}{\sin(\pi+4h)} = \frac{\cos(4h)}{\sin(4h)} = \frac{1}{4h} +o\left(\frac{1}{h}\right)$$

Now $$\lim\limits_{h \to 0} (1-2h)^{\frac{1}{4h}} = 1/\sqrt{e}$$ which is the limit you're looking for.

$\endgroup$
  • 1
    $\begingroup$ @ReinhardMeier Thanks for spotting the mistake. I'll update the answer. $\endgroup$ – mathcounterexamples.net Oct 15 '19 at 12:07
  • $\begingroup$ I have deleted my comment now that you have updated the answer. $\endgroup$ – Reinhard Meier Oct 15 '19 at 12:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.